Distance Learning in Physical Education: Hindsight Is 2020 — Part 3. Issue 4 (4th May 2021) - Goad, Tyler; Killian, Chad M.; Daum, David N.
Abstract: Over 40 years ago physical education pedagogy researchers Anderson and Barrette asked the question, "What's going on in Gym?" This inquiry sparked widespread research and innovation that moved our field forward. Today, physical educators are faced with a new reality of teaching movement-based content remotely and the question has now shifted to, "What's going on in Online Physical Education?" During the Spring of 2020 and into the Fall, many physical educators had to rapidly transform their face-to-face lessons to a virtual environment. In the previous two parts of this three-part series, frequently asked questions related to distance learning in physical education have been addressed. These previous parts addressed instructional strategies and pedagogical considerations related to the unique aspects of teaching physical education remotely during the pandemic. The purpose of this article is to provide teachers with guidance and resources to consider how to adapt pandemic pedagogies to enhance student learning in their face-to-face classes when that inevitability occurs.